ANALISIS PENGELOLAAN BADAN USAHA MILIK DESA DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DESA (Studi Pada BUMDes Rekso Wijoyo di Desa Tambong Kecamatan Kabat Kabupaten Banyuwangi) - Erlina Anjarrini; Dimas Imaniar; Bambang Wicaksono (Jawa Dwipa, 2025)
This research aims to determine and describe the management of the Village-Owned Enterprise (BUMDes) Rekso Wijoyo in efforts to increase the Original Income of Tambong Village, Kabat District, Banyuwangi Regency. The study uses a qualitative approach with a narrative study. Data collection was conducted through observation, interviews, and documentation. The research results, based on the seven management principles according to Luther Gulick, show that the management of BUMDes in an effort to increase the village’s original income includes: (1) Planning: BUMDes Rekso Wijoyo faces challenges such as limited capital and business licensing issues; however, in 2025, BUMDes will focus on utilizing available resources through a food security program, involving the participation of various parties, including the community; (2) Organizing: The organization of BUMDes Rekso Wijoyo is still simple but is updated annually to support ongoing programs; (3) Staffing: The recruitment process at BUMDes Rekso Wijoyo is not open due to limited funds, but human resource development is carried out through training; (4) Directing: The director's guidance is effective, with a focus on improving the village economy; (5) Coordinating: BUMDes Rekso Wijoyo involves all parties and prioritizes transparency in every collaboration; (6) Reporting: Financial reporting is still simple using Excel, but accountability reports are made transparently to relevant stakeholders; and (7) Budgeting: There are several obstacles, such as limited capital and ineffective financial management, but BUMDes Rekso Wijoyo continues to monitor and evaluate to address the ongoing issues. Effective management processes and functions are required for BUMDes Rekso Wijoyo in its efforts to increase the Original Income of Tambong Village, Kabat District, Banyuwangi Regency."